Critical Pedagogy in Islamic Education: Re-examining the Thought of Paulo Freire and Ibn Khaldun for Liberatory Learning - Dian Nopita Sari; Sefri Kandi Ja’far Yazid; Adelia Syafitri; Atmajaya; Akbar Maulidin; Irma; Muhammad Abid Fathin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Contemporary Islamic education frequently struggles with authoritarian, rote-learning practices that fundamentally contradict its emancipatory theological ideals. This study aims to resolve this pedagogical stagnation by synthesizing Paulo Freire’s critical pedagogy with Ibn Khaldun’s humanistic educational philosophy. Employing a qualitative library research method with a comparative-philosophical approach, the study critically analyzes primary texts and recent scholarly literature published between 2019 and 2024. The findings reveal that while Freire offers robust socio-political conscientization, it inherently lacks spiritual depth. Conversely, Ibn Khaldun provides essential psychological safety and gradual learning but requires a critical edge for modern social justice. By integrating both paradigms, this research proposes a novel conceptual framework termed